Study of Beach Litter on Remote Island, Case Study: Ainoshima Island, Japan - Nani Anggraini; Irfan Tawakkal; Muhammad Ma‘arij Harfadli; Sattar Yunus; Indriyani Rachman; Toru Matsumoto (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2023)
Ainoshima Island is a Remote Island located north of Kyushu Island which is also known as a popular tourist attraction named Cat Island. The island is inhabited by a small population but is frequented by tourists to enjoy nature and fishing. The coastline is in the form of cliffs and sandy beaches, but there is a lot of marine debris on the sandy beaches. In addition, its location allows waste from the surrounding area to be carried by currents to this island. This research examines the diversity of categories and types of macroplastic litter trapped on the sandy beach of Ainoshima Island. Survey transects were conducted in the spring of 2023 via visual observation based on a survey method developed by NOAA, in 2012. The survey results were then categorized based on a photo guide database from the OSPAR Maritime Area for Active Monitoring of Marine Debris on the Beach. Data on the types of waste found are divided into artificial polymer materials (plastic), rubber, cloth, paper/cardboard, processed/finished wood, metal, glass, and ceramics. As a result, the plastic category is the dominant category of the total type of waste trapped in sandy beach areas.